PENGARUH KEMAMPUAN DAN PERILAKU GURU TERHADAP KUALITAS PELAYANAN PENDIDIKAN - Dekawati, Ipong (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2018)
This research has been carried out and analyzed by taking the main focus on the ability and behavior of teachers and their impact on the quality of education services. The method used is the explanatory survey method where the author went directly to the empirical level by spreading the questionnaire to 40 teachers at the State Elementary School. The technique of processing and analysis used is regression. The results showed that: (1) There is a positive and significant influence ability of teachers on the quality of education services at the State Elementary School. The amount of influence of the teacher's ability on the quality of education service is 32.1%. (2) There is a positive but less significant effect of teacher behavior on the quality of education service at the State Elementary School. The amount of influence of teacher behavior on the quality of education service is 3.7%. (3) There is a positive and significant influence teacher's ability and teacher's behavior together towards the quality of education service. The amount of influence of teacher ability and teacher behavior simultaneously on the quality of education service is 32,6%. Moving from the conclusion of the research that has been stated above, humbly the writer suggest that: (1) The result of research has shown that operationally both teacher ability and teacher behavior and quality of education service have been quite good. But as the development of community demands in the future it should not be satisfied until the present condition. It is recommended that the principal together with the teacher continue to improve the quality of education services in a sustainable manner with the development of teachers through participation in scientific forums so that the knowledge, insight and ability of teachers can keep abreast of developments. (2) It can be proved that both the ability and behavior of teachers affect the quality of education services. Therefore, to always maintain or improve the quality of education services that can be started by improving the ability and behavior of teachers through special attention to the needs and desires of consumers.